The supply of Accounting graduates in New Zealand - Wells, Paul (AUT Faculty of Business, 2005)
Declining enrolments in accounting programmes in the United States of America and United Kingdom have been well documented for over a decade and it is suggested that accounting as a career choice is becoming less attractive to domestic students. An Australian study supported this conclusion but further noted that the trend is being masked by an increasing level of enrolments in these programmes by international students. Collectively these studies highlight the vulnerability of accounting programmes to fluctuation in the recruitment and enrolment of international students and further, a potential decline in the number of domestic graduates seeking employment in the accounting profession. This study reports the collection and analysis of data from 8 of the 14 approved tertiary education institutions that provide a recognised academic programme to meet the CA requirements of the Institute of Chartered Accountants of New Zealand (ICANZ). Its objectives are to identify graduation trends for the period 1997-2002 and to consider the impact of international student enrolment on these trends. The findings suggest that there have been significant fluctuations in the number of accounting graduates since 1997, with domestic graduate numbers rising between 1999 and 2001 and then declining in 2002. During this time the total number of business graduates has remained constant. The decline in graduate numbers coincides with the introduction of the four-year programme of study. As a consequence the findings reported here have implications for the tertiary education institutions, ICANZ and employers.